(3GdCfS GdLdjd HJGQjN GdbOS hGdNdjds - (3YHO GdQMef Hf eMeO Hf YHO GdQMef GdoYndrjej GdMfHdj, nCoHh Gdojref, eLjQ GdOjf,J (B928 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdeJaVd Ydi Ndbg HaJM CHhGH GdQMeI CeG HYO , agPG eNJUQ ESJNQJ Gddg ai LeYg jJVef JGQjN GdHjJ GdebOS Yf di Cf CLeYg ef cJH GdeJbOejf , hCgPH CdaGXg ef cJH GdeDQNjf s
(3BNQgG (B:s
(3hef EfTGOg ai HjJ GdebOS HYO ZjHI Yfg eOI WhjdI hbO SeYJgG ef daXg HOQH GdbOS Mjf YhOg ef ZRI GdeMQhSI hEf aSM Gddg ai GdCLd LYdJ dg PjdkG CPcQ ajg eG jbY ef GdMhYOK HGdbOS ef Chd SfI EMOi hJSY eFI Edi BNQ hbJ jQjO Gddg JYGdi ef GdYes
(3HChdgG Jedc SfI (B1107(3g` TQY GdeDda ai JCdjag ai TgQ Pi GdMLI SfI (B900 (3ai GdeYgO fSNI CNQi HQbe (B69 (3JGQjNs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B331 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B177s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B43 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B2 - (3bSe (B5 s
(3eUOQ GbJfGA GdCUd (B:s
(3QhSjG (B(611 b) s
Keywords: (3GdJGQjNs